The State of the Art of Radiotherapy for Non-melanoma Skin Cancer: A Review of the Literature - Benkhaled, Sofian; Van Gestel, Dirk; Gomes da Silveira Cauduro, Carolina; Palumbo, Samuel; Marmol, Veronique del; Desmet, Antoine (Frontiers in Medicine, 2022)
Due to the general aging population and the fashion trend of sun exposure, non-melanoma skin cancer (NMSC) is rising. The management of NMSCs is difficult and necessitates a multidisciplinary team (i.e., pathologists, dermatologists, medical oncologists, surgeons, radiation oncologists). When surgery is not an option or will cause unacceptably functional morbidity, radiation (RT) may be a preferable tissue-preserving option. Whether used alone or in conjunction with other treatments, RT has been demonstrated to be quite effective in terms of cosmetic results and local control. Contact hypofractionated RT, brachytherapy, and electronic brachytherapy are all promising new treatments. However, rigorous, randomized trials are missing, explaining the disparity in dose, fractionation, and techniques recommendations. Therefore, it is essential that interdisciplinary teams better understand RT modalities, benefits, and drawbacks. Our review will provide the role and indications for RT in patients with NMSC.